Neuroprotective effect of vitamin D3 toward apoptosis induced by ethanol in CA1 pyramidal cells of rat hippocampus - Dwi Cahyani Ratna Sari, Junaedy Yunus Djoko Prakosa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
As an antioxidant, Vitamin D3 can protect neurons from damage caused by oxidative stress.Ethanol is known to have neurotoxic effects by inducing an increase in oxidative stress. One ofthe brain regions that is most sensitive to neurotoxic effects induced by ethanol is hippocampus,especially its CA1 region. This study was aimed to determine the neuroprotective effects ofvitamin D3 in preventing the apoptosis in CA1 hippocampal pyramidal cells induced by ethanol.Fifteen male Wistar rats (Rattus norvegicus) were randomly divided into three groups. The controlgroup was given daily normal saline solution intraperitoneally. The ethanol group was given20% ethanol solution at a dose of 3 g/kg BW/day intraperitoneally. The vitamin D3 group wasgiven vitamin D3 1 μg/kg BW/day in 20% ethanol solution at a dose of 3 g/kg BW/dayintraperitoneally. After 30 days, the rats were sacrificed, their brains were perfused with PBSfollowed by fixative and the hippocampus was dissected for histological preparations.Immunohistochemical staining for caspase was performed. Percentage of apoptotic CA1hippocampal pyramidal cells was calculated. The results showed there was no significant difference(p> 0.05) on the total number of pyramidal cells between the control group (20.52 ± 1.31), theethanol group (19.02 ± 1.60), and the vitamin D3 group (21. 06 ± 0.70) per field of view.However there was a significant increase (p<0.05) in the percentage of apoptotic CA1hippocampal pyramidal cells in in the ethanol group (16.09 ± 0.67%) compared to the controlgroup (10.60 ± 0.95%). Vitamin D3 significantly (p<0.05) prevented an increase in the percentageof apoptotic CA1 hippocampal pyramidal cells in the vitamin D3 group (10.82 ± 0.64%). Inconclusion, vitamin D3 had a neuroprotective effect to prevent an increase in apoptosis in CA1hippocampal pyramidal cells to the neurotoxic effects induced by ethanol.